Stability analysis for grain yield and quality traits in selected traditional and improved varieties of rice over different Zones of Karnataka - Ashwini, G L; Rajanna, M P; Deepak, CA; Chethana, BS; Shobha, D; Gouda, TH; Dushyanthkumar, BM; Hanamaratti, NG; Ramesh, S; Nagaraj, MS; Mahantashivayogayya, KH (ORYZA-An International Journal of Rice, 2019)
Traditional rice varieties (TRVs) form important components of genetic reservoir. TRVs used in study viz., Rajamudi, Ratnachoodi and Jeerigesanna are photosensitive. They may exhibit Genotype by Environment (G×E) interactions for grain yield and quality traits. Hence, present experiment was conducted to understand responses of yield and quality traits in selected traditional along with improved varieties of rice over five different locations of Karnataka using additive main effects and multiplicative interaction (AMMI) model and bi-plots were developed following GGE bi-plot methodology. AMMI analysis revealed that there existed significant GE interaction among ten rice varieties and genotypes and environments were diverse in nature. IPCA1 and IPCA2 together explained more than 75% of GE interaction for yield and quality traits and maximumGE interaction was explained by IPCA (Interaction Principle Component Analysis) 1. BR-2655 and Ratnachoodi were found to be most stable varieties and Mugadsiri was found to be most unstable variety for grain yield. Jeerigesanna and BPT-5204 were stable for gel consistency and amylose content respectively. Among rice varieties used, BR-2655 was found to be the best variety since it recorded highest grain yield and also it was stable performer for grain yield and also amylose content across five different locations.